COGNITIVE DYSFUNCTION IN SUBCLINICAL HYPOTHYROIDISM USING AUDITORY P300 EVOKED POTENTIALS-SYSTEMATIC REVIEW AND META-ANALYSIS - KRISHNAMURTHY SOUNDARIYA; REENAA MOHAN; JENIFER FLORENCE MARY; DEEPIKA VELUSAMI (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Subclinical hypothyroidism, an early and mild form of hypothyroidism rarely presents with clinical manifestations. Literature search has revealed conflicting results on cognitive dysfunction in subclinical hypothyroidism. While the majority of studies used neuropsychiatric tests for cognitive assessment, we aimed to study the cognitive function in subclinical hypothyroidism using evoked potentials “P300.” The data sources used were Google Scholar, PubMed, MEDLINE, and Cochrane which were rigorously searched until March 2024. The meta-analysis includes all published studies that used P300 evoked potential to assess cognitive performance in subclinical hypothyroidism. A specified checklist supervised the data extraction process. Using RevMan 5 software, mean P300 at Cz values were aggregated from the chosen trials. The differences in P300 at Cz between normal and subclinical hypothyroidism were evaluated. Data analyses were conducted till March 2023. The current meta-analysis was done using 4 studies with 156 subjects with subclinical hypothyroidism and 182 apparently healthy subjects showed a significant increase in P300 latency in subclinical hypothyroidism (mean difference (MD)=21.65, 95% confidence interval [CI] 0.37–42.92, p<0.00001) at Cz. There was a significant decrease in P300 amplitude in subclinical hypothyroidism compared to healthy subjects at Cz (MD=−0.31, 95% CI −1.08 −0.47, p<0.33). Our study results suggest that subclinical hypothyroidism is associated with cognitive dysfunction as evidenced by the prolongation of the P300 latency. However, there is a need for analysis of more prospective cohort studies.